2003
DOI: 10.1161/01.cir.0000094397.19932.78
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Receptor Blockers in Cardiovascular Disease

Abstract: Abstract-The endothelin (ET) system is comprised of 4 active ETs, with ET-1 being the predominant isoform in the cardiovascular system. Because of the potent vasoconstricting and mitogenic effects of ET-1 and its involvement in various cardiovascular diseases, blockade of the ET receptor has received considerable attention. ET receptor antagonism has been demonstrated to be beneficial in patients with pulmonary hypertension. The nonselective ET receptor antagonist bosentan improves exercise capacity and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(139 citation statements)
references
References 77 publications
3
128
0
8
Order By: Relevance
“…A conceivable usefulness of ET-receptor antagonists in the treatment of hypertension (64,71), chronic or acute heart failure (77) has not been established and currently does not seem to be promising.…”
Section: Discussionmentioning
confidence: 99%
“…A conceivable usefulness of ET-receptor antagonists in the treatment of hypertension (64,71), chronic or acute heart failure (77) has not been established and currently does not seem to be promising.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our data suggest that the renal medullary ET B receptors may be a potential target for treatment of hypertension. Thus far, clinical studies utilizing ET-1 receptor blockers have shown little effect on blood pressure in hypertensive patients (22); however, the early ET-1 receptor blockers used were either combined ET A / ET B blockers or were ET A blockers, which lacked in vivo specificity (4). Because of the natriuretic and antihypertensive properties of ET B receptors, blockade of ET B receptors in these studies may have counteracted any beneficial effects of ET A receptor blockade.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Endothelin-1 is a vascular regulator that is produced by endothelial cells and cardiomyocytes, which has vasoconstrictive and mitotic effects via the stimulation of growth factors. It is also important in hypertension, acting as a blood pressure elevator (13,14). CD68, which belongs to the LAMP (lysosomal-associated membrane protein) family of glycoproteins, is expressed by monocytes and macrophages.…”
Section: Introductionmentioning
confidence: 99%